2021
DOI: 10.52198/21.sti.38.cv1413
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art Review: Surgical Treatment of Acute Type A Aortic Dissection

Abstract: Acute type A aortic dissection (ATAAD) is a life-threatening event that requires immediate surgical treatment. Improvements in surgical treatment, graft technology, organ protection and imaging techniques have led to improved clinical outcomes. Individualized treatment concepts have emerged based on more advanced planning tools that allow for a tailored approach even in complex situations such as multi-level malperfusion. This review provides an overview of the current surgical treatment of ATAAD, focusing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 92 publications
0
18
0
Order By: Relevance
“…An interesting finding in the reports of the AMDS device is the resolution of the dissection involving the supra-aortic vessels following the procedure. Montagner et al 8 and Mehdiani et al 29 reported the resolution of malperfusion involving the supra-aortic vessels in all patients in their respective independent cohorts. Bozso et al 27 reported that 95% of preoperatively identified malperfused vessels were re-perfused post-operatively.…”
Section: The Darts Trialmentioning
confidence: 94%
See 3 more Smart Citations
“…An interesting finding in the reports of the AMDS device is the resolution of the dissection involving the supra-aortic vessels following the procedure. Montagner et al 8 and Mehdiani et al 29 reported the resolution of malperfusion involving the supra-aortic vessels in all patients in their respective independent cohorts. Bozso et al 27 reported that 95% of preoperatively identified malperfused vessels were re-perfused post-operatively.…”
Section: The Darts Trialmentioning
confidence: 94%
“…However, patients who are implanted with the AMDS device must undergo open hemi-arch replacement prior to the antegrade introduction of the bare stent into the arch, which has been associated with inferior outcomes relative to FET. 7,8 Thoraflex hybrid in clinical practice Since its introduction in 2010, THP quickly established itself as the eminent device for the treatment of complex aortic arch pathologies. 9 The FET procedure using THP has yielded consistent and positive short-and long-term outcomes, leading to its rising acceptance in the surgical community over the other available devices.…”
Section: Ascyrus Medical Dissection Stent (Amds)mentioning
confidence: 99%
See 2 more Smart Citations
“…Although acute type A aortic dissection (ATAAD) is rare, it is a possibly lethal event that presents cardiac surgeons with major challenges [ 1 , 2 , 3 ]. Even though ATAAD is still associated with high mortality and morbidity rates, thirty-day mortality has dropped to an average of 17% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%